Penanaman Karakter Siswa pada Pembelajaran Pendidikan Pancasila dan Kewarganegraan - Husna, Asmaul; Nuraini, Nuraini; Marhamah, Marhamah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
his study aims to determine the form of instilling the character of discipline and responsibility in students through learning Pancasila and Citizenship Education. This research uses descriptive qualitative method using qualitative data. The subjects of this study were students of class IV consisting of 2 people, class V consisted of 2 and class VI consisted of 2 people so that the number of students studied amounted to 6 students. Data collection techniques used the approach of observation, interviews, and documentation. Data reduction was carried out and then analyzed and verified using source triangulation. The findings of this study are that the character of discipline and responsibility of students is always given and instilled by the teacher both during class hours and outside class hours, because the character of discipline and responsibility is very important given to students in their development period. There are supporting and inhibiting factors for teachers in instilling the character of student discipline and responsibility. Efforts are being made to overcome the inculcation of the character of discipline and responsibility. Keywords: Character, Discipline, Responsibility